(3bdGFO GdYbjGf aj eMGSf GdQDSGA hGdbVGI hGdcJGH hGdGYjGfs - (3GHf NGbGf , CHh fUQ,J (B528 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QGVi dfG GdHjGf MJi GfbGO ai hHYO aEf GdGOH GLed eG GdJMbg GdgeI hYQaJg GdGeI s
(3BNQgG (B:s
(3ef CHjGJ jGFjI dYHO Gddg Hf YGFTI hdjS SGHM Gf JYPHJ ai Gdghi aMjjJ ef CLd GdMHjH GdeZGfjG s
(3GdfSNI HgG MhGTs
(3HGdfSNI GKGQ JbWjY ai GdhQbGJ GdChdis
(3hdhf GdhQb OGcf hCQVjJg Hfi ai HYV GdUaMGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B134 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B49s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1354s
Keywords: (3GdCOHs